2023
DOI: 10.1108/ajms-03-2022-0052
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic analysis of a prey–predator population model with a nonlinear harvesting rate

Abstract: PurposeIn this article, the author discusses dynamical behaviors of a prey-predator population model with nonlinear harvesting rate and offers a mathematical analysis of the model.Design/methodology/approachThe design is by using modelization of populations interaction, qualitative theory of ordinary différential equations, bifurcations analysis, invariant center manifolds theory and Dulac's criterion.FindingsThe author studies the stability of solutions and the existence of periodic solutions in the model, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The stability criteria of this model was also examined for this model. Finally, Mohdeb [10] explored the stability of fixed points and the occurrence of periodic solutions for a prey-predator model including nonlinear harvesting effect. Transcritical and saddle node bifurcations were also discussed in [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability criteria of this model was also examined for this model. Finally, Mohdeb [10] explored the stability of fixed points and the occurrence of periodic solutions for a prey-predator model including nonlinear harvesting effect. Transcritical and saddle node bifurcations were also discussed in [10].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Mohdeb [10] explored the stability of fixed points and the occurrence of periodic solutions for a prey-predator model including nonlinear harvesting effect. Transcritical and saddle node bifurcations were also discussed in [10]. More studies about predator-prey model can be found in refs.…”
Section: Introductionmentioning
confidence: 99%